Comparative study of chromatographic properties of affinity resins in respect of protein of antithrombin III - М. А. Аzhigirova; T. L. Dereza; I. S. Кryazhevskikh; N. V. Sergeeva; V. I. Shvets (Тонкие химические технологии, 2010)
This paper reports the chromatographic properties of affinity resins in respect of protein antithrombin III. The capacity of resin Toyopearl AF-Heparin was found to be higher than that of resin of Heparin-Sepharose FF. Sorption was carried out by the batch method at room temperature and constant stirring. The specific activity of antithrombin III was estimated by the amidolytic method with the use of a chromogenic substrate. The obtained results can be used for the development of column chromatographic method of isolation of antithrombin III from human plasma.